2016
DOI: 10.1080/03009734.2016.1228721
|View full text |Cite
|
Sign up to set email alerts
|

Differential neutrophil chemotactic response towards IL-8 and bacterial N-formyl peptides in term newborn infants

Abstract: BackgroundA prerequisite for an effective innate immunity is the migrative ability of neutrophils to respond to inflammatory and infectious agents such as the intermediate interleukin (IL)-8 and the end-target formyl-methionyl-leucyl-phenylalanine (fMLP) chemoattractants. The aim was to study the chemotactic capacity of neutrophils from newborn infants and adults in response to IL-8 and the bacterial peptide fMLP.MethodsIn the under-agarose cell migration assay, isolated leukocytes from healthy adults and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…In the present study, CD44 receptors in resting neutrophils from neonates were also fewer than in adults, a finding not previously described. As CD44 plays an essential role for migrating neutrophils, the reduced number of receptors could contribute to the reduced migration in response to IL‐8 observed in our previous study . Similar to other studies, the expression of CD64 on resting neutrophils from neonates was higher than in adults (Table ) .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the present study, CD44 receptors in resting neutrophils from neonates were also fewer than in adults, a finding not previously described. As CD44 plays an essential role for migrating neutrophils, the reduced number of receptors could contribute to the reduced migration in response to IL‐8 observed in our previous study . Similar to other studies, the expression of CD64 on resting neutrophils from neonates was higher than in adults (Table ) .…”
Section: Discussionsupporting
confidence: 88%
“…Our observation that the response to intermediate chemoattractants is compromised in newborn infants is supported by Urlichs et al [18]. In a previous study, we observed that IL-8 induced a markedly lower chemotactic response in neutrophils from newborns than from adults in terms of the amount of chemotactic cells and the distance of migration [2]. On the other hand, the same neutrophil receptor expression changes were observed in neonates and adults in response to fMLP, for all the receptors involved in adhesion, chemotaxis, granula activation and phagocytosis (Table 3b).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations